FAKTOR YANG MENYOKONG PEREMPUAN PENIAGA MINANGKABAU BERNIAGA SENDIRIAN DI PASAR TRADISIONAL MINANGKABAU - Midawati (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2021)
Minangkabau people, both men and women, have long been known to have trade skills. The ability to trade is supported by the number of traditional markets in Minangkabau called feed, almost in all nagari. In traditional markets, women dominate as traders. This study looked at women who trade in the Baso market. The results of the study found that there are several factors that support women to become traffickers, namely cultural factors, family support, infrastructure, small capital, access to financial sources and security.